Finance, Labour, Capital, and International Integration - Giuseppe Bertola (Center for Economic Studies and ifo Institute (CESifo), 2016)
Labour incomes depend on structural as well as politico-economic factors, because labour market policies partially remedy the financial market imperfections that make labour income shocks difficult to insure, and have different implications for labour and capital income. This paper illustrates such theoretical insights with a simple model, and reviews evidence of their empirical relevance generated by international economic, monetary, and financial integration.
Keywords: D33; 330